Катаболітна деградація фруктозо-1,6-бісфосфатази у метилотрофних дріжджів Pichia pastoris і Hansenula polymorpha - Дмитрук, О.В.; Сибірний, А.А. (Фактори експериментальної еволюції організмів, 2014)
Aim. Fructose-1,6-bisphosphatase (FBPase) which is synthesized when cells are grown on non-fermentable carbon sources. When yeast cells are subsequently shifted to a glucose-containing medium, FBPase is rapidly inactivated and degraded. This process is called catabolite degradation. Methods. Standart molecular biological and biochemical methods were used. Results. The wild type strains of P. pastoris and H. polymorpha were analyzed by Western blot, using the antibodies for FBP protein of S. cerevisiae. It was shown that FBPase is mostly degraded after 5 hours of incubation of cells in glucose-containing medium. After shifting the cells from methanol or ethanol-containing media on glucose medium, FBPase activity of P. pastoris and H. polymorpha wild-type strains decreased 4.5–5 and 2–2.5 times, respectively. Conclusions. The recombinant strains of P. pastoris with the deletion of FBP gene were constructed and analyzed. Δfbp strains did not grow in the medium with non-fermentable carbon sources. To study the mechanisms of catabolite degradation, plasmids for the expression of FBP fused with GFP were constructed. The recombinant strains with the expression of these plasmids were obtained and analyzed.

Key words: yeasts, fructose-1,6-bisphosphatase, catabolite degradation.